INTEGRATIVE APPROACH AS A BASIS FOR FORMING COMPETENCE (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
New generation standards based on a competency-based approach are entering the system of higher professional education. In this regard, it should be emphasized that even a thorough study of the very structure of professional competence and the competencies included in it, which has been actively carried out recently by many specialists, does not in itself allow us to answer the most important question: how exactly, with the help of what mechanisms, to form this competence? Competence as a systemic new formation cannot arise instantly.